Molecular characterisation of the broad‐spectrum resistance to powdery mildew conferred by the Stpk‐V gene from the wild species Haynaldia villosa. (26th September 2017) - Qian, C.; Cui, C.; Wang, X.; Zhou, C.; Hu, P.; Li, M.; Li, R.; Xiao, J.; Wang, X.; Chen, P.; Xing, L.; Cao, A.
Abstract: A key member of the Pm21 resistance gene locus, Stpk‐V, derived from Haynaldia villosa, was shown to confer broad‐spectrum resistance to wheat powdery mildew. The present study was planned to investigate the resistance mechanism mediated by Stpk‐V . Transcriptome analysis was performed in Stpk‐V transgenic plants and recipient Yangmai158 upon Bgt infection, and detailed histochemical observations were conducted. Chromosome location of Stpk‐V orthologous genes in Triticeae species was conducted for evolutionary study and over‐expression of Stpk‐V both in barley and Arabidopsis was performed for functional study. The transcriptome results indicate, at the early infection stage, the ROS pathway, JA pathway and some PR proteins associated with the SA pathway were activated in both the resistant Stpk‐V transgenic plants and susceptible Yangmai158. However, at the later infection stage, the genes up‐regulated at the early stage were continuously held only in the transgenic plants, and a large number of new genes were also activated in the transgenic plants but not in Yangmai158. Results indicate that sustained activation of the early response genes combined with later‐activated genes mediated by Stpk‐V is critical for resistance in Stpk‐V transgenic plants. Stpk‐V orthologous genes in the representative grass species are all located on homologous group six chromosomes, indicating that Stpk‐V is an ancient gene in the grasses. Over‐expression of Stpk‐V enhanced host resistance to powdery mildew in barley but not in Arabidopsis . Our results enable a better understanding of the resistance mechanism mediated by Stpk‐V, and establish a solid foundation for its use in cereal breeding as a gene resource.